KETEPATAN WAKTU ATAS LAPORAN KEUANGAN PERUSAHAAN INDONESIA - BANDI; SANTOSO TRI HARTANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
Many of researches on the market capital reactions have been conducted, both in Indonesia and in other countries. Surprisingly, there is little empirical evidence of such research investigates the timeliness of the Indonesian annual reports, brief research methodology is needed especially associated with market reactions. The result of this study shows generally the distributions of timeliness of the Indonesia firm's financial statement announcement positively skewed, it is consistent with prior research (Dyer and McHugh, 1975). In addition in term of company size the result indicates that there are not significant differences. Further more, unlike the results of the study by Chambers and Penman (1984) this study shows that the reports published earlier than expected have price effects not differ with when they of sum sample and by sensitivity test there is different market reactins of them.